Interaction of Chelating Agent Aluminon and Iron(III) Ions on 3a Zeolite: A Study By Photometric and X-Ray Diffraction Methods - Prasad Banerjee, Sati (Asian Journal of Chemistry, 2010)
Interaction of aluminon with 3A zeolite followed by addition of Fe(III) ions brings about changes in the composition and structure of the zeolite. Aluminon-3A zeolite behaves as the collecting agent for the precipitation of the hydroxide of Fe(III). Results of photometric and X-ray diffraction studies of the two new coloured derivatives of 3A zeolite have been reported together with their composition data.